2007
DOI: 10.1088/0953-4075/40/20/009
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of Stark states of hydrogenic atoms and ions

Abstract: The motivation for this work is the problem of providing accurate values of the atomic transition matrix elements for the Stark components of Rydberg–Rydberg transitions in atomic hydrogen and hydrogenic ions, for use in spectral line broadening calculations applicable to cool, low-density plasmas, such as those found in H II regions. Since conventional methods of calculating these transition matrix elements cannot be used for the high principal quantum numbers now easily attained in radio astronomical spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(75 citation statements)
references
References 52 publications
0
75
0
Order By: Relevance
“…As was found for the observations below ∼ 3 GHz, the 6 GHz data also show an unexplainable line narrowing. This mysterious result has since been examined by several authors (Hey 2006(Hey , 2007(Hey , 2009Watson 2006;Oks 2004;Griem 2005;Gigosos et al 2007;Gavrilenko and Oks 2007;Gordon 2008;von Prochazka et al 2010) but all attempts to explain it as an impact narrowing for quantum numbers above n = 200 and above ∆n = 8 have been unsuccessful. Although the reduced impact broadening below 3 GHz might be explainable by variable density models, this is unlikely to be the explanation for the decrease seen at 6 GHz since these observations were all made with the same telescope, the same beamwidth, and near the same frequency.…”
Section: Data At 6 Ghzmentioning
confidence: 98%
“…As was found for the observations below ∼ 3 GHz, the 6 GHz data also show an unexplainable line narrowing. This mysterious result has since been examined by several authors (Hey 2006(Hey , 2007(Hey , 2009Watson 2006;Oks 2004;Griem 2005;Gigosos et al 2007;Gavrilenko and Oks 2007;Gordon 2008;von Prochazka et al 2010) but all attempts to explain it as an impact narrowing for quantum numbers above n = 200 and above ∆n = 8 have been unsuccessful. Although the reduced impact broadening below 3 GHz might be explainable by variable density models, this is unlikely to be the explanation for the decrease seen at 6 GHz since these observations were all made with the same telescope, the same beamwidth, and near the same frequency.…”
Section: Data At 6 Ghzmentioning
confidence: 98%
“…The quantum mechanical solutions of the hydrogen atom in parabolic coordinates have been described in detail in Ref. [16]. For the Rydberg-Stark problem we use the parabolic coordinates defined as ξ ± = x 2 + y 2 + z 2 ± z , ξ 0 = arctan (y/x) .…”
Section: Theory a Semiclassical Approachmentioning
confidence: 99%
“…Further studies of the relationship between the quantum states in these representations are found in Refs. [16,20]. A discussion of features of the lifetimes of m = 0 vs m = 0 Stark states was given in Ref.…”
Section: Theory a Semiclassical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, radiative transitions originating from high-n levels of hydrogen or hydrogen-like ions have a complex structure of the Stark effect, which poses a few calculational challenges. While effective and accurate methods for evaluating the atomic transition matrix elements are now readily available [10], the complexity due to the large number of different atomic states involved in such a transition remains an impeding factor in applying computer simulation methods employing directly solving the timedependent Schrödinger equation for Stark broadening of highn transitions in plasmas. The fast growth of the computational requirements with n makes such calculations unfeasible for, say n 20, using present personal computers.…”
Section: Introductionmentioning
confidence: 99%